From technology to market: a bibliometric and integrative review on autonomous vehicles. (30th March 2020) - Silva, João Paulo Nascimento Da; Gandia, Rodrigo Marçal; Sugano, Joel Yutaka; Oliveira, Cledison Carlos; Antonialli, Fabio; Pedrosa, Gabriel; Antunes, Luiz Guilherme Rodrigues; Cavazza, Bruna Habib
The present study aims to understand the direction that research on autonomous vehicles (AVs) has taken in the academy, in order to bring to surface and detail gaps on the disruptive aspect of this innovative sector. A bibliometric revision was used to map the research present in the Clarivate Analytics Web of Science database, followed by a systematic integrative review to structure the evolution of the research and present the main aspects. Five categories that show the evolution of the research on AV technology were retrieved, such as a new focus on the users of technology. We also identified gaps in each category on how this technology should reach the market. Additionally, it was also possible to draw a global view of the technology development landscape by the analysis of both academic and market data, according to the KPMG report, and also to identify the recent market trend of mobility as a service (MaaS).